2017
DOI: 10.1002/path.4987
|View full text |Cite
|
Sign up to set email alerts
|

A new model system identifies epidermal growth factor receptor-human epidermal growth factor receptor 2 (HER2) and HER2-human epidermal growth factor receptor 3 heterodimers as potent inducers of oesophageal epithelial cell invasion

Abstract: Oesophageal squamous cell carcinomas and oesophageal adenocarcinomas display distinct patterns of ErbB expression and dimers. The functional effects of specific ErbB homo- or heterodimers on oesophageal (cancer) cell behaviour, particularly invasion of early carcinogenesis remains unknown. Here, a new cellular model system for controlled activation of EGFR or HER2 and EGFR/HER2 or HER2/HER3 homo- and heterodimers was studied in non-neoplastic squamous oesophageal epithelial Het-1A cells. EGFR, HER2 and HER3 in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
4
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 57 publications
2
4
0
Order By: Relevance
“…Of note, these patient samples pre-date the clinical use of trastuzumab. Other studies have shown positive and negative associations between ΔNp63/p40 and HER2 (or other ERBB family members) [18,23,[40][41][42] and it is therefore likely that HER2-ΔNp63/p40 crosstalk accounts for our observations. Investigation of ΔNp63/p40 as a marker of improved prognosis deserves further study, potentially in the setting of HER2 directed clinical trials.…”
Section: Discussionsupporting
confidence: 53%
“…Of note, these patient samples pre-date the clinical use of trastuzumab. Other studies have shown positive and negative associations between ΔNp63/p40 and HER2 (or other ERBB family members) [18,23,[40][41][42] and it is therefore likely that HER2-ΔNp63/p40 crosstalk accounts for our observations. Investigation of ΔNp63/p40 as a marker of improved prognosis deserves further study, potentially in the setting of HER2 directed clinical trials.…”
Section: Discussionsupporting
confidence: 53%
“…MCF10A cells overexpressing either HER2 or an activating Mek mutant also showed reduced ΔNp63 levels in 3D suspension culture, and Mek inhibition increased ΔNp63 in HER2‐overexpressing cells [129]. EGFR/HER2 activation also decreased p63 in non‐neoplastic squamous oesophageal cells [130]. To add further confusion, mutant RasG12V increased and a dominant negative Ras mutant decreased ΔNp63 activity in HaCaT keratinocytes [131], whilst EGF treatment of MCF10A cells [132] and mutant K‐RasG12D in prostate basal cells increased ΔNp63 levels [94].…”
Section: Signalling Pathways That Regulate P63 Levels or Activitymentioning
confidence: 99%
“…Activating the laminin receptor increased ΔNp63 levels in keratinocytes [203] and integrin‐linked kinase (ILK) inhibition reduced ΔNp63 [204]. The ECM component TGFBIp increased ΔNp63 in limbal epithelial cells, also linked to FAK activation [205], whilst decreased FAK was associated with ΔNp63 downregulation in oesophageal squamous cells with EGFR/HER2 activation [130]. These cell–cell and cell–matrix interactions may account for some of the discrepancies on p63 regulation, where growth factors, TGFβ, and other stimuli may cause EMT‐induced loss of cell–cell and/or cell–ECM signalling.…”
Section: Signalling Pathways That Regulate P63 Levels or Activitymentioning
confidence: 99%
“…In a study performed by Chiou et al (2008), the expression of EGFR1 was increased in nearly 90% of the OSCC cases. Aggressive tumor behavior, radiation resistance, and poor prognosis are associated with the enhanced expression of EGFR1 (Fichter et al, 2017;Olayioye, Neve, Lane, & Hynes, 2000). EGFR activates several downstream pathways through binding to growth factors and causing conformational changes in the extracellular domain (Sandfeld-Paulsen, Folkersen, Rasmussen, Meldgaard, & Sorensen, 2016).…”
Section: Epidermal Growth Factor Receptormentioning
confidence: 99%
“…Moreover, such mutations predispose to numerous malignancies including breast, lung, colorectal, stomach, pancreatic, oral and head and neck cancers (Hynes, 2016). Fichter et al (2017) demonstrated that the activation of EGFR, HER2, and HER3 homo-and hetero-dimers resulted in the migration and invasion of epithelial cells. They concluded that ErbB homo-and hetero-dimers played a key role in most cancers.…”
Section: Epidermal Growth Factor Receptormentioning
confidence: 99%